Examining the Readability Level of Reading Texts in English Textbook for Indonesian Senior High School - Adib Aminul Hakim; Endang Setyaningsih; Dewi Cahyaningrum (English Department - University of Sultan Ageng Tirtayasa, 2021)
Assuming that textbooks authors have conducted the readability measure, many of its users often take this key feature of a good textbook for granted. Nonetheless, considering the unique context of each classroom and the generic nature of textbooks written for the public, teachers should double-check the appropriateness of the book they use, including its readability. Although tech-assisted readability measurement is developing in many parts of the world, in Indonesia, this area is still under-researched. For this reason, the present study attempts to examine the readability level of an English textbook using Coh-Metrix. Content analysis is employed since the object being analyzed is a textbook. This study also expands previous studies on readability measures by building dialogue between the result of Coh-Metrix measurement and the students’ perceived readability. To obtain the data, an automated Coh-Metrix readability measurement was conducted via cohmetrix.com. Also, to get more profound analysis, a questionnaire on students’ perceived readability was distributed to 35 tenth graders. Then the collected data were analyzed by using interactive model of Miles and Huberman. The finding of this study revealed that regardless of the slight difference between the perceived readability level and the Coh-Metrix-generated readability level, most of the texts in the book are mostly below the students’ level. Arguably, the textbook is relatively potential for language acquisition because it provides comprehensible input.